The Basic Research of the Combinatorial Therapy of ABT-199 and Homoharringtonine on Acute Myeloid Leukemia - Shi, Yuanfei; Ye, Jing; Yang, Ying; Zhao, Yanchun; Shen, Huafei; Ye, Xiujin; Xie, Wanzhuo (Frontiers in Oncology, 2021)
Background: Existing research shows that ABT-199, as a first-line drug, have been widely used in hematological malignancies, especially in leukemia, but the clinical efficacy of single drug therapy was limited part of the reason was that BCL-2 inhibitors failure to target other anti-apoptotic BCL-2 family proteins, such as MCL-1. In this case, combination therapy may be a promising way to overcome this obstacle. Here, we investigate the preclinical efficacy of a new strategy combining ABT-199 with homoharringtonine (HHT), a selective inhibitor of MCL-1 may be a promising approach for AML treatment as these two molecules are important in apoptosis. Methods: A Cell Counting Kit-8 (CCK8) assay and flow cytometry were used to determine the half-maximal inhibitory concentration (IC50) value and cell apoptosis rate, respectively. The flow cytometry results showed that combined treatment with HHT and ABT-199 caused apoptosis in AML patient samples (n=5) but had no effect on normal healthy donor samples (n=11). Furthermore, we used a Western blot assay to explore the mechanism underlying the efficacy of HHT combined with ABT-199. Finally, antileukemic activity was further evaluated in vivo xenograft model. Results: Our results indicated that ABT-199 combined with HHT significantly inhibited cell growth and promoted apoptosis in both AML cell lines and primary AML tumors in a dose- and time-dependent manner. Moreover, HHT combined with ABT-199 suppressed AML cell growth and progression in vivo xenograft model. Conclusions: Our research found that HHT combined with ABT-199 exerted its anti-leukemia effect by inducing apoptosis through the treatment of AML in vitro and in vivo.